Optimizing Sunburn Prevention in Children: A Meta-Analysis of the Efficacy of Sunscreen Application, Protective Apparel, and Shade-Seeking Behaviors - Ellistasari, Endra Yustin; Suci Widhiati; Sesia Pradestine (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Childhood sunburn significantly elevates lifelong skin cancer risk, underscoring the need for effective prevention. While sunscreen, protective apparel, and shade-seeking are advocated, a quantitative synthesis of their efficacy in children is crucial. This meta-analysis aimed to consolidate and quantify the evidence on the effectiveness of these core sun protection strategies in preventing pediatric sunburn. Methods: A systematic search of PubMed/MEDLINE, Scopus, Cochrane CENTRAL, and Web of Science (January 2014 - December 2024) identified randomized controlled trials and cohort studies evaluating sunscreen, protective apparel, or shade-seeking behaviors for sunburn prevention in individuals aged 0-18 years. Data on sunburn incidence were extracted, study quality assessed, and pooled Risk Ratios (RR) with 95% confidence intervals (CI) calculated using a random-effects model. Results: Six studies (two RCTs, four cohort studies) involving 8,500 children were included. Regular sunscreen use (SPF ≥30) significantly reduced sunburn incidence (RR 0.65, 95% CI 0.55-0.77). Protective apparel use also demonstrated substantial protection (RR 0.70, 95% CI 0.60-0.82). Enhanced shade provision and shade-seeking behaviors effectively lowered sunburn risk (RR 0.75, 95% CI 0.62-0.90). Multi-component strategies combining these approaches showed consistent protective benefits. Conclusion: This meta-analysis provides robust quantitative evidence that diligent sunscreen application, consistent use of protective apparel, and active shade-seeking are all significantly effective in reducing sunburn incidence in children. These findings strongly support multifaceted public health initiatives emphasizing comprehensive sun protection to safeguard pediatric skin health.